(untitled) (TEST Ticontre. Theory Text Translation, 2026)
This paper examines the phototextual strategies employed by Benedetta Tobagi in La Resistenza delle donne (Einaudi, 2022), a hybrid work in which the dialogic interplay between visual and essayistic narrative codes reshapes the historical discourse on women’s Resistance. The analysis is framed within two theoretical axes: visual culture and phototext theory on one hand, and critical reflection on the essay as a liminal literary form on the other. Through a montage-based structure, the interweaving of oral, memorial, and literary sources, and the author-narrator’s discursive stance, the work constructs a polyphonic and counter-hegemonic memory. The phototext thus emerges as a critical device capable of redefining the relationship between testimony and representation, between the visible and the sayable, within an intermedial perspective that questions the very genealogy of historical narration.